Percorsi di diritto comparato - Cerchia, Rossella Esther (Milano University Press, 2021)
The book Percorsi di diritto comparato (Paths of Comparative Law) is based on the papers delivered in 2020 as part of the course of the Comparative Law curriculum of the Doctorate School of Comparative, Private, Civil Procedure and Business Law at the University of Milan. The volume consists of twelve essays, which aim to offer a cross-section of some of the topics that animate the comparative law reflections, addressing issues of great topicality in the doctrinal debate, national and international.